The Question of the vis-à-vis: Scotland and Others - David McCRONE (E-REA)
The essence of identity is ‘othering’. Who we are not matters as much as who we take ourselves to be. Identities – including those of nation, class, gender and ‘race’ – do not stand alone, but are to be understood in the context of the vis-à-vis. The upsurge in ‘being English’, for example, has come about in the context of not being ‘European, crystallised in the 2016 Brexit debate and vote, and the rise of right-wing Conservatism in England. ‘Being Scottish’, on the other hand, has been reinforced contra this English turn, and as a result, Scots have become more ‘European’.From the outset, at least from the 14th century, Scots were a ‘mongrel people’, defined by territorial/civic rather than cultural/ethnic characteristics, as a matter of raison d’être. This generated, pari passu, a sense of belonging based as much on who we were not (English) as who we thought ourselves to be (Scots). None of this is to deny ‘being British’ except insofar as state-identity (British) has become aligned with being English. Thus, the alignment of ‘England’ and voting Leave in the 2016 Brexit referendum is a case in point. The strong Remain vote in Scotland was an assertion of institutional Scottishness even if highly personal. Since 2016, the connection between being Scottish, voting Remain, and being in favour of Scottish independence within the EU has strengthened. Similarly, Scottish Government has been able to draw upon levels of political and social trust in the context of the Covid-19 pandemic, reinforcing the point that ‘national identities’ are in essence about materialities rather than simply emotions, of politics as much as culture; the key lies in the relationship between them.